Aceh-Nias reconstruction and rehabilitation: Progress and challenges at the end of 2006 - Suahasil Nazara; Budy P. Resosudarmo (Asian Development Bank Institute (ADBI), 2007)
This study examines the recovery and reconstruction experience of Indonesia, following the December 2004 Asian tsunami that destroyed much of Aceh island, inflicting some 167,000 fatalities and destroying much of the island's housing and infrastructure. This was followed soon after by a major earthquake in the neighbouring island of Nias. A large reconstruction programme was launched by the government, with pledges from international donors to meet most of the reconstruction costs. The changed approach in Aceh following the tsunami paved the way for a peace settlement that ended a decades-long military conflict in the province. However, two years after the tsunami key reconstruction plan targets have not been met and are unlikely to be met in the foreseeable future. The Indonesian experience highlights coordination problems between the many government agencies, international donors, and NGOs; difficulties for reconstruction agencies in using funds effectively; and the dangers of a large funding gap emerging because of underestimation of local cost increases. Lessons and implications are drawn for institutional development and policy formulation to cope with future natural disasters. These have relevance not only for Indonesia but also for many other developing countries.
Keywords: Q54; F35; H54; I38; O19; 330; Überschwemmung; Makroökonomischer Einfluss; Gesellschaft; Wirtschaftslage; Aceh; Indonesien